Nonstandard Use of the “Reflexive” Affix -sja in Russian Speech of Bilingual Speakers of Northern Siberia and the Russian Far East - Irina Khomchenkova; Polina Pleshak; Natalia Stoynova (Languages, 2019)
One of the features of the oral Russian speech of bilingual speakers of the indigenous languages of Russia is the omission/the overuse of the “reflexive” affix -sja (a “middle voice” marker with a wide range of uses including reflexive, reciprocal, anticausative, passive, and some others). We discuss the data on the nonstandard use of -sja in the Russian speech of bilingual speakers of two language groups that differ both from Russian and from each other in this grammatical domain: Samoyedic (Forest Enets, Nganasan, and Nenets) and Tungusic (Nanai and Ulch). The data come from the corpus of contact-influenced Russian speech, which is being created by our team. We show that the mismatches in standard and nonstandard usage cannot be explained by direct structural copying from the donor language (indigenous) to the recipient one (the local variety of Russian). Nor is there a consistent system which differs from standard Russian since there are many more usages that follow the rules of standard Russian. The influence of the indigenous languages explains some overuses and omissions; the others can be explained by other factors, e.g., difficulties in the acquisition of verb pairs with non-transparent semantic or syntactic relations.